The princess and the frog [videorecording (DVD)] - Clements, Ron; Musker, John; Rose, Anika Noni, 1972-; Campos, Bruno; David, Keith; Wooley, Michael-Leon; Cummings, Jim, 1952-; Lewis, Jenifer, 1957-; Winfrey, Oprah; Howard, Terrence; Goodman, John, 1952-; Newman, Randy (Walt Disney Studios Home Entertainment : Distributed by Buena Vista Home Entertainment, 2010)
New Orleans. Arrogant, carefree Prince Naveen and hardworking waitress Tiana cross paths. Prince Naveen is transformed into a frog by a conniving voodoo magician. Tiana follows suit when she decides to kiss the amphibian royalty. With the help of a trumpet-playing alligator, a Cajun firefly, and an old blind lady who lives in a boat in a tree, Naveen and Tiana must race to break the spell and fulfill their dreams.